Removal of cadmium and zinc from water using sewage sludge-derived biochar - Shah, Ahsan; Zakharova, Julia; Batool, Maryam; Coley, Matthew P.; Arjunan, Arun; Hawkins, Alisha J.; Bolarinwa, Timothy; Devi, Shreah; Thumma, Anusha; Williams, Craig (Sustainable Chemistry for the Environment, 2024)
This research reveals the adsorption of cadmium (Cd2+) and zinc (Zn+2) from water using sewage sludge-derived biochar pyrolysed at 700 °C (SSB). The morphology and particle characteristics of SSB were characterised through scanning electron microscopy (SEM), particle size distribution (PSD), fourier transform infrared (FTIR), X-ray diffraction (XRD), and X-ray fluorescence (XRF). The adsorption study showed that the optimum contact times for removing Zn2+ and Cd2+ were 80 and 140 minutes, respectively. 95.51% Zn2+ and 97.54% Cd2+ could be removed from spiked solutions featuring 50 mg/L of Zn2+ and 50 mg/L Cd2+, each treated with 25 g/L biochar. The optimum pH of the solutions was 8–9 at a temperature of 40°C, indicating some precipitation of the metal ions at an alkaline pH. The highest adsorption capacity of SSB for Cd2+ and Zn2+ was found to be 3.02 and 2.51 mg/g, respectively, which compares favourably with other adsorbents. The isotherm studies confirmed experimental data to closely follow the Langmuir isotherm model at an R2 value of 0.9846 and 0.9816 for Cd2+ and Zn2+, respectively. The kinetic study confirmed the physical interaction between the adsorbents and the adsorbate. The spontaneous and exothermic nature of the process was confirmed by negative values of change in Gibbs free energy (ΔG) and enthalpy (ΔH). SSB could be regenerated for 6 cycles. Overall, this study explores sustainability, recycling, and waste management by offering SSB as a potentially cost-effective and environment-friendly solution to remove Cd2+ and Zn2+ from water. [Display omitted] •Non-modified biochar was used to adsorb Cd and Zn.•Process fits well to pseudo-first order model and follows Langmuir Isotherm model.•Fitness of experimental data was validated by using five error analysis models.•Adsorption capacity was 3.02 mg/g and 2.51 mg/g for Cd and Zn respectively.•Adsorption Process was spontaneous, exothermic and feasible.